Transcriptome analysis during vernalization in wheat (Triticum aestivum L.) - Jiao Wang; Lei Sun; Hongwei Zhang; Bo Jiao; Haibo Wang; Shuo Zhou (BMC Genomic Data, 2023)
Abstract Background Vernalization, as a vital process in the life cycle of winter cereal, has important effects on floral organ formation and flowering time. Many morphological changes together with molecular changes occur during the vernalization period. Here, we used transcriptome sequencing to analyze the transcriptomic changes in wheat leaves before, during and after vernalization using the winter wheat cultivar ‘Shiluan02-1’. Results A total of 16,370 differentially expressed genes were obtained across different vernalization periods. Gene Ontology enrichment analysis revealed that photoperiodism, photoprotection, photosynthesis, lipid transport and biosynthetic process, and chlorophyll metabolic process were closely related to vernalization. In addition, AP2/ERF, C2H2, bHLH, WRKY, MYB, MYB-related, and NAC transcription factors were significantly enriched during vernalization, and the transcription factor expression patterns suggested the intricate regulation of transcription factor modules in plant vernalization pathways. Analysis of gene expression patterns of the MADS-box transcription factor genes showed different expression patterns during vernalization phases, among which VERNALIZATION1 (VRN1) genes were found to gradually increase during vernalization periods from V0 to V35, while decline in the V42 phase, then increase after vernalization. The Tavrt-2 gene cooperated with Tavrn1 to regulate flowering induced by vernalization, and its expression level was rapidly increased by vernalization but declined in the V42 phase and then increased after vernalization. Some genes from the ICE-CBF-COR pathway were also identified, and additional analysis indicated that some key genes related to phytohormone biosynthesis and signal transduction were enriched during the vernalization period, such as gibberellic acid, ethylene, abscisic acid and jasmonic acid biosynthesis and signaling pathway genes. Conclusions Our study provides valuable molecular information for future studies on wheat vernalization regulation and also serves as an excellent reference for future wheat breeding.